The dangers of gadget addiction on the mental health of rural adolescents in Ciamis District - Zen, Dini Nurbaeti; Wibowo, Daniel Akbar; Lesmana, Indra (Science Midwifery, 2024)
The increasing use of gadgets among Indonesian teenagers, with 98.3% using mobile phones, has raised concerns about its impact on mental health. Studies indicate that excessive gadget use can lead to anxiety, depression, sleep disorders, social isolation, poor academic performance, and problematic behavior. However, public awareness of these risks remains low, particularly in Ciamis Regency, where no definitive data on gadget addiction and mental health exists. This study aims to assess the prevalence of gadget addiction and its impact on adolescent mental health in Ciamis Regency through a cross-sectional observation of 100 teenagers aged 13-18 years. Socio-demographic factors such as age, gender, school type, parental occupation, and academic performance were analyzed, along with variables like gadget type, usage duration, internet activity, and parental or teacher supervision. To measure gadget addiction, the SASSV Scale was used, while mental health was assessed through the Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire (PHQ-9) for depression. The study found a strong correlation between gadget dependence and mental health, with anxiety (correlation coefficient of 0.794) and depression (0.619) both significantly linked to gadget use. The findings highlight the negative effects of uncontrolled gadget use on adolescent mental well-being, particularly regarding anxiety. Key influencing factors include the frequency, type of application used, and duration of gadget use. The study emphasizes the need for effective strategies to manage gadget use among adolescents to mitigate these mental health risks.